Behavioral Neuroscience of Learning and Memory (Current Topics in Behavioral Neurosciences,, 2018)
'Behavioral Neuroscience of Learning and Memory' brings together the opinions and expertise of some of the world's foremost neuroscientists in the field of learning and memory research. The volume provides a broad coverage of contemporary research and thinking in this field, focusing both on well established topics such as the medial temporal lobe memory system, as well as emerging areas of research such as the role of memory in decision making and the mechanisms of perceptual learning. Key intersecting themes include the molecular and cellular mechanisms of memory formation, the multiplicity of memory systems in the brain, and the way in which technological innovation is driving discovery. Unusually for a volume of this kind, this volume brings together research from both humans and animals-often relatively separate areas of discourse-to give a more comprehensive and integrated view of the field. The book will be of interest to both established researchers who wish to broaden their knowledge of topics outside of their specific areas of expertise, and for students who need a resource to help them make sense of the vast scientific literature on this subject.